Ab initio study of the structural, magnetic, and electronic properties of copper and silver clusters and their alloys with one palladium atom - S. J Hashemifar; H Najafvandzadeh; H Kahnouji; H Akbarzadeh (Iranian Journal of Physics Research, 2015)
In this paper, the structural, magnetic, and electronic properties of two- to nine-atom copper and silver clusters and their alloys with one palladium atom are investigated by using full-potential all-electron density functional computations. After calculating minimized energy of several structural isomers of every nanocluster, it is argued that the small size nanoclusters (up to size of 6), ‎ prefer planar structures, while by increasing size a 2D-3D structural transformation is observed. The structural transformation of pure and copper-palladium clusters occurs in the size of seven and that of silver-palladium cluster in happens at the size of six. The calculated second difference and dissociation energies confirm that the two- and eight- atom pure clusters and three- and seven- atom alloyed clusters are magic clusters. The electronic and magnetic properties of stable isomers are calculated and considered after applying many body based GW correction.